Cross-border health care in the European Union : mapping and analysing practices and policies - Wismar, Matthias (WHO Regional Office for Europe, 2011)
Cross-border health care is a growing phenomenon in the European Union. When in need of medical treatment, patients increasingly act as informed consumers who claim the right to choose their own providers, including those beyond borders. They are supported and encouraged by factors such as the Internet and more internationally trained health professionals, and often motivated by dissatisfaction with health care provision in their home country. Some authorities and health insurers even contract with health care providers abroad or inform patients of such options.Cross-border health care also encompasses doctors and nurses, who train and work abroad and increasingly cooperate with colleagues abroad. In some cases, health services themselves cross borders—through telemedicine—or providers collaborate with financing institutions in other countries. This book explores these trends, looks at the legal framework and examines the legal uncertainties surrounding rights, access, reimbursement, quality and safety. It examines different approaches to these concerns and the methodologies used to ease or resolve them. The information and analysis presented mark an important step in the continuing debate on a legal framework for cross-border health care and will be of considerable use to policy-makers and those with an interest in key aspects of cross-border health care.
Observatory studies series ; no. 22
Keywords: emigrace a imigrace; Health Services Accessibility; veřejné zdravotnictví; Health Policy; poskytování zdravotní péče; kvalita zdravotní péče; Delivery of Health Care; European Union; Evropa; zdravotní politika; Emigration and Immigration; Quality of Health Care; mezinárodní spolupráce; International Cooperation; dostupnost zdravotnických služeb; Europe; Evropská unie